PROBLEM SOLVING USING SELF-GENERATED DATA: LEARNING CONCEPT OF SPEED AT UPPER PRIMARY STAGE - Prabha, Shashi (European Scientific Journal, ESJ, 2015)
Working on self-generated data contextualizes learning and students see relevance of their learning in their day-to-day life. An attempt has been made to examine, ‘can solving problems using self- generated data by performing activities facilitate students at upper primary stage to learn concept of speed in better way?’ It is observed that this approach can bridge the gap between their classroom experiences and everyday life experiences and remove fear of solving numerical problems. The study highlights the importance of actively engaging the students in the construction of knowledge and learning scientific concepts by self-generated data. Teachinglearning of science needs to be transformed from the process of knowledge transfer to knowledge generation.